The Depiction of Non-Verbal Communications in Raymond’s Run Short Story - Suharto, Ririn Pratiwi (ESENSI LINGUA, 2023)
The data of this research was taken from Raymond’s Run by T. C. Bambara. This short story is interesting because it contains several verbal communications. This research aims to identify non-verbal communication di Raymond’s Run Short Story. This is library research. The result of this study is there are seven types of nonverbal communication are found in the short story, which include kinesics (body movement and facial expression), physical characteristics, proxemics (space), chronemics (time), paralanguage, artifacts, and environment. It is found that kinesics (body movements and facial expressions) is the most dominant type of nonverbal communication in that short story.